Green building certificate systems as a greenwashing strategy in architecture - Kurnaz, Ahmet; Kurnaz, Ahmet (Bartın Üniversitesi, 2021)
As a result of the depletion of natural resources, the destruction of green, the damage of the ecosystem, and having less habitable areas each passing day, the concept of sustainability has become an important parameter at every stage in the architecture field, from decisions related to planning and design to practice of those. All these reasons have led the way to establish green building standards and green building certification systems to reduce the negative implications of buildings on the natural environment through sustainable design. Today, green building evaluation systems have some practical problems. Recently, the increase in the tendency towards making green buildings with the purpose of advertising through the effective use of social media channels and the transformation of tendency into green building sector itself and into greenwashing strategies is the most important discussion point of the study. In the study, the concepts of sustainability, green building and green building certification systems were examined in detail, green building projects and certification systems that claim sustainability were discussed, and a theoretical perspective on green building certification systems as a greenwashing strategy in the field of architecture was introduced by referring to the evolution of environmental activist movements. Within the scope of this study, it was aimed to measure the consistency of the criteria of the green building evaluation systems that evaluate the green status of buildings on certain criteria such as LEED and BREEAM, which are becoming widespread on a global scale, by examining these systems in detail.
Keywords: Architecture; Green building; Green building certificate system; Greenwashing; LEED; BREEAM